2016
DOI: 10.1177/0044118x16662749
|View full text |Cite
|
Sign up to set email alerts
|

Age of Alcohol Initiation Matters: Examining Gender Differences in the Recency and Frequency of Alcohol Use Across Adolescence Using a Sample of Impoverished Minority Adolescents

Abstract: While previous research has shown alcohol use to increase developmentally throughout adolescence, the age of alcohol initiation has rarely been incorporated into developmental trajectories. Simultaneous estimation of the effects of early alcohol initiation was made in relation to the recency and frequency of alcohol use utilizing a sample of 1,209 low-income, minority adolescents initiating alcohol between 12 and 18. Significant effects of both age of alcohol initiation and gender were found. Initial alcohol u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…Several recent studies have used prospective data to examine the relation between early substance use initiation and later progression patterns. Analyses have identified escalated alcohol use frequency among early initiators (Bolland et al, 2016), as well as gender (Tomek et al, 2016) and racial/ethnic (Malone, Northrup, Masyn, Lamis, & Lamont, 2012) differences in alcohol use trajectories following initiation. Behrendt, Wittchen, Höfler, Lieb, and Beesdo (2009) found that later ages of substance use onset were associated with faster transition to SUD, with the exception of DSM–IV cannabis dependence.…”
mentioning
confidence: 99%
“…Several recent studies have used prospective data to examine the relation between early substance use initiation and later progression patterns. Analyses have identified escalated alcohol use frequency among early initiators (Bolland et al, 2016), as well as gender (Tomek et al, 2016) and racial/ethnic (Malone, Northrup, Masyn, Lamis, & Lamont, 2012) differences in alcohol use trajectories following initiation. Behrendt, Wittchen, Höfler, Lieb, and Beesdo (2009) found that later ages of substance use onset were associated with faster transition to SUD, with the exception of DSM–IV cannabis dependence.…”
mentioning
confidence: 99%
“…This population is of particular interest given the commonly discussed gaps in opportunities evidenced among racial and ethnic minorities, as well as the importance of early alcohol initiation on negative outcomes (CDC, 2010; Donovan & Molina, 2011; Griffin et al, 2010; Swahn et al, 2010; Windle & Windle, 2012). As opposed to treating alcohol initiation as a dichotomous variable in our analysis, we will allow the age of alcohol initiation to factor into the model, therefore concurrently analyzing both the short-term and the long-term effects of alcohol initiation at all ages (Singer & Willett, 2003; Tomek et al, 2019). We hypothesize that earlier initiation will indeed have a negative effect on school outcomes.…”
Section: The Current Studymentioning
confidence: 99%
“…Future studies should explore how societal socioeconomic conditions could affect drinking trajectories. Lastly, since the ED-dependence association might differ between genders (Tomek et al, 2016), we characterized the association by gender. The results were similar for males, but not for females.…”
Section: Relationships Between Ed and Dependence For All Countries Anmentioning
confidence: 99%
“…Additionally, although alcohol use among females has increased over time and ED has grown among them, evidence regarding the link between ED and later trajectories of alcohol use and related problems between genders has also been contradictory (Tomek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation